The transformation strategy of radio Republik Indonesia in attracting interest of the youth: case study of RRI Central Java - Yuni Wulandari,; Ade Wahyudin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This qualitative study, adopting a SWOT analysis methodology, critically examines Radio Republik Indonesia (RRI), focusing on its Central Java branch, as one of the regions that still hold closely to its culture and traditions - to transform strategically to engage the youth effectively. Identifying key weaknesses, including RRI's formal broadcasting style, regulatory constraints, and misalignment of content production with the preferences of the youth demographic, the research underscores the urgency for RRI to pivot towards a more relaxed, contemporary, and interactive broadcasting approach. The study advocates for a comprehensive strategy encompassing active audience participation and using digital platforms such as RRI Digital and RRI Play Go. These platforms present opportunities for RRI to enhance content accessibility and relevance, catering to the dynamic consumption patterns of the youth. The article posits that a robust transformation strategy should address broadcasting style restructuring and necessitate technological upgrades. Fostering collaboration with creative communities is essential for creating content that resonates with the youth. The study delves into the significance of strategic digital marketing, leveraging the strengths of social media and other digital platforms where the youth are most active. By incorporating these elements, the research proposes a holistic transformation strategy, offering actionable insights for RRI in adapting to the evolving preferences of the youth. This contribution extends beyond the case of RRI Central Java, serving as a valuable resource in the ongoing discourse surrounding public broadcasting strategies in the digital era.